Adsorbate induced core level shifts of transition metal surfaces - Nilsson, Viktor (My University, 2013)
A shift in the core electron binding energy detected with X-ray photoelectron spec- troscopy (XPS) gives insight into the local chemical configuration of atoms. Such infor- mation can be used, for instance, to determine the surface structure upon adsorption. By comparing the experimental spectra with theoretical predictions, the core level shifts can be attributed to specific atomic configurations. In this thesis, core level shifts for metal surfaces upon adsorption have been computed by electronic structure calculations within density functional theory (DFT), using the software VASP. The transition metals Ni, Cu, Ru, Rh, Pd, Ag, Cd, Pt and Au have been investigated in terms of their surface structure and adsorption sites for CO, H, O and S have been tested. Core level shifts for the hcp(0001)/fcc(111) and fcc(100) facets have been deter- mined for each adsorbate. Since the involved mechanisms contributing to these energy shifts are difficult to decouple, trends among shifts as well as a model for explaining them have been sought. A clear dependence on coordination number is seen, where the binding energy is lower for a lower coordination. Trends depending on element are also found. The shift upon adsorption is towards higher binding energies for almost all elements and adsorbates. Notable exceptions are Ag and Cd. The correlation between d-band centre shift and core level shift is confirmed whereas the common model of viewing charge transfer as a dominant effect for the shifts is found insufficient.
Keywords: Kemisk fysik; Ytor och mellanytor; Elektronstruktur; Beräkningsfysik; Kvantkemi; Chemical physics; Surfaces and interfaces; Electronic structure; Computational physics; Quantum chemistry